Akuntabilitas Kinerja Pemerintah Daerah: Suatu Studi Fenomenologi di Kota Manado Sulawesi Utara - Supriati, Arie (Universitas Brawijaya, Indonesia, 2016)
This study aimed to uncover, explain, and know the implementation of performance and financial accountability of local governments in Manado, the phenomenon of irregularities and violations of the use of budget revenues and expenditures.The method in this study is qualitative research with phenomenological approach. The results showed that the main causes of irregularities and violations of the use of budget funds at Manado North Sulawesi province is the lack of adequate personnel resources executive, weak supervision and lack of socialization implementation system of performance accountability of government agencies. Strategic planning did not synergy with the mission and objectives, performance measurement did not using clear standard, performance reporting did not entirely based on the Government Performance Accountability System. The role of Regional Head quite efective in the implementation of the accountability of local government performance at Manado. Audit Reports from the Supreme Audit Agency, Fiscal year 2011, received no opinion reasonable (adversed).